Patient and public involvement in emergency care research. Issue 9 (4th April 2016) - Hirst, Enid; Irving, Andy; Goodacre, Steve
Abstract : Patients participate in emergency care research and are the intended beneficiaries of research findings. The public provide substantial funding for research through taxation and charitable donations. If we do research to benefit patients and the public are funding the research, then patients and the public should be involved in the planning, prioritisation, design, conduct and oversight of research, yet patient and public involvement (or more simply, public involvement, since patients are also members of the public) has only recently developed in emergency care research. In this article, we describe what public involvement is and how it can help emergency care research. We use the development of a pioneering public involvement group in emergency care, the Sheffield Emergency Care Forum, to provide insights into the potential and challenges of public involvement in emergency care research.